Is metal contamination responsible for increasing aneuploidy levels in the Manila clam Ruditapes philippinarum? - Piló, David (2019)
The present study assessed the metal genotoxicity potential at chromosome-level in the bivalve Ruditapes philippinarum collected along different areas of the Tagus estuary. Higher levels of aneuploidy on gill cells were detected at the most sediment contaminated area both in May (31.7%) and October (36.0%) when compared to a less contaminated area over the same periods (203% and 29.0% respectively). Interestingly, metal bioaccumulation in gills was higher in the specimens collected at the least contaminated area with the exception of Pb. Indeed, the multivariate analysis revealed a stronger relation between aneuploidy and sediment contamination than between aneuploidy and the bioaccumulation of the metals. The temporal and spatial inconsistency found for the bioaccumulation of metals in It philippinarum and the positive correlation between sediment contamination and aneuploidy at the most contaminated area suggest that these chromosome-level effects might be due to chronic metal contamination occurring in the Tagus estuary, rather than a direct result of the temporal variation of bioavailable contaminants. The vertical transmission phenomenon of bivalve aneuploidy levels may then be perpetuating those levels on clams from the most contaminated area. The present results shed light about the effect of metal toxicity at the chromosome-level in species inhabiting chronic contaminated areas and highlight the use of aneuploidy as an effective tool to identify persistent contamination in worldwide transitional waters. (C) 2016 Elsevier B.V. All rights reserved.